2006
DOI: 10.1007/s00122-006-0426-8
|View full text |Cite
|
Sign up to set email alerts
|

Local genetic diversity of sorghum in a village in northern Cameroon: structure and dynamics of landraces

Abstract: We present the first study of patterns of genetic diversity of sorghum landraces at the local scale. Understanding landrace diversity aids in deciphering evolutionary forces under domestication, and has applications in the conservation of genetic resources and their use in breeding programs. Duupa farmers in a village in Northern Cameroon distinguished 59 named sorghum taxa, representing 46 landraces. In each field, seeds are sown as a mixture of landraces (mean of 12 landraces per field), giving the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
106
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(122 citation statements)
references
References 41 publications
14
106
1
1
Order By: Relevance
“…The high variability observed by this study can be attributed to farmers' practice of interspecific intercropping of sorghum landraces, which increases the chances of gene flow within and outside the genotypes (Barnaud et al, 2007). Seed exchange among farmers could be another contributing factor to high variation among sorghum landraces.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The high variability observed by this study can be attributed to farmers' practice of interspecific intercropping of sorghum landraces, which increases the chances of gene flow within and outside the genotypes (Barnaud et al, 2007). Seed exchange among farmers could be another contributing factor to high variation among sorghum landraces.…”
Section: Discussionmentioning
confidence: 73%
“…Both morphological and molecular markers are used to save this purpose. Morphological characterisation was the first method used by researchers to select superior genotypes, spring wheat (Briggs, 1991), barn swallows (Cadee, 2000), and maize (Beta and Corke, 2001;Geleta and Labuschagne, 2005;Barnaud et al, 2007). However, several studies show that morphological markers are not suitable for traits with low heritability and are highly affected by environments (Smith and Smith, 1992;Redfearn et al, 1999;Cadee, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Billot et al (2013) found similar result on a collections maintained by self-pollination. In contrast, high Ho value (0.11) was observed by Barnaud et al (2007) when assessing samples obtained directly from landraces. Local accessions contain an important number of private alleles whereas no private alleles were observed in improved varieties.…”
Section: Discussionmentioning
confidence: 81%
“…As in other large-scale assessments of sorghum genetic diversity (9,11,12), we included one individual per accession to infer population structure, and, as in ref. 8, we included more than one individual per seed lot for local-scale calculation of diversity indices, F ST among landraces, and NJ analysis.…”
Section: Methodsmentioning
confidence: 99%